Dendritic growth gated by a steroid hormone receptor underlies increases in activity in the developing Drosophila locomotor system - Zwart, Maarten F.; Evers, Jan-Felix (Proceedings of the National Academy of Sciences of the United States of America, 2013)
As animals grow, their nervous systems also increase in size. How growth in the central nervous system is regulated and its functional consequences are incompletely understood. We explored these questions, using the larval Drosophila locomotor system as a model. In the periphery, at neuromuscular junctions, motoneurons are known to enlarge their presynaptic axon terminals in size and strength, thereby compensating for reductions in muscle excitability that are associated with increases in muscle size. Here, we studied how motoneurons change in the central nervous system during periods of animal growth. We find that within the central nervous system motoneurons also enlarge their postsynaptic dendritic arbors, by the net addition of branches, and that these scale with overall animal size. This dendritic growth is gated on a cell-by-cell basis by a specific isoform of the steroid hormone receptor ecdysone receptor-B2, for which functions have thus far remained elusive. The dendritic growth is accompanied by synaptic strengthening and results in increased neuronal activity. Electrical properties of these neurons, however, are independent of ecdysone receptor-B2 regulation. We propose that these structural dendritic changes in the central nervous system, which regulate neuronal activity, constitute an additional part of the adaptive response of the locomotor system to increases in body and muscle size as the animal grows.